2019
DOI: 10.1002/jmri.26904
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of 3D texture analysis: A multicenter MRI study of the brain

Abstract: Background Texture analysis (TA) is an image‐analysis technique that detects complex intervoxel statistical patterns. 3D TA has shown potential in detecting cerebral degeneration not perceptible to the human eye in many neurological disorders. The reliability of this method's application in a multicenter study is unknown. Purpose To assess the intrasite and intersite reliability of a novel 3D TA method from data acquired systematically from the Canadian ALS Neuroimaging Consortium (CALSNIC). Study Type Prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Several important findings were made in this study. The phantom developed in this study has several advantages over previous test objects 15,[33][34][35][36][37][38][39] and can be used for radiomics analysis. It is stable and can be printed to create customized shapes and patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Several important findings were made in this study. The phantom developed in this study has several advantages over previous test objects 15,[33][34][35][36][37][38][39] and can be used for radiomics analysis. It is stable and can be printed to create customized shapes and patterns.…”
Section: Discussionmentioning
confidence: 99%
“…CALSNIC publications are forthcoming that report results from multicentre MRS, 15 DTI, 27 structural, 24 texture, 41,43 , and neuropathology data. The richness and extensiveness of the data provides a unique opportunity for advanced analytical methods (multivariate classifiers, AI) to help discriminate biological variability.…”
Section: Discussionmentioning
confidence: 99%
“…The travelling head images are available to derive scaling and corrective factors to transform data from sites into a common data space prior to analysis, and to assess inter-site and intra-site variance. The travelling head data was used for reliability assessments for MRS, 15 DTI, 27 and texture 41 modalities.…”
Section: Methodsmentioning
confidence: 99%
“…Ta et al mentioned that 3D texture analysis has the potential for the detection of cerebral degeneration which is not easily noticeable for the naked eye. They have found that 3D texture analysis has shown potential and enough reliability that it can be used for longitudinal studies [24].…”
Section: Related Workmentioning
confidence: 99%